Risk Factors for the Development of Obstetric Pathologies in Women with Outflow of Amniotic Fluid (Eurasian Medical Research Periodical, 2023)
The article presents the results of a gynecological and somatic history. A gynecological history was burdened in 71.7% of the subjects: chronic inflammatory diseases of the appendages, and vagina in 37.7% diseases of the cervix in 25.5%, uterine fibroids in 5.7% and ovarian cysts in 2.8%. Overweight somatic history was 81.1% of pregnant women. The most frequent pathologies among the examined patients were: Iron deficiency anemia in 36.8%, and diseases of the urinary system in 10.4%. Clinical and anamnestic risk factors for pregnant women complicated by premature rupture discharge of amniotic fluid are a history of endometritis, pathological growth of conditionally pathogenic cervicovaginal microflora, chlamydia, nonspecific vaginal inflammation.